The Application of Diabatic Heating in Q-Vectors for the Study of a North American Cyclone Event - Katie L. Crandall; Patrick S. Market; Anthony R. Lupo; Laurel P. McCoy; Rachel J. Tillott; Justin J. Abraham (Advances in Meteorology)
An extended version of the Q-vector form for the ω-equation that includes diabatic (in particular latent) heating in the Q-vector itself is derived and tested for use in analyzing the life-cycle of a midlatitude cyclone that developed over the central United States during 24–26 December 2009. While the inclusion of diabatic heating in the Q-vector ω-equation is not unique to this work, the inclusion of diabatic heating in the Q-vector itself is a unique formulation. Here it is shown that the diabatic Q-vector gives a better representation of the forcing contributing to the life-cycle of the Christmas Storm of 2009 using analyses derived from the 80-km NAM.